PENERAPAN MESIN PENGOLAH PUPUK ORGANIK DI DESA KEJI UNGARAN BARAT - Petrus - Maharsi (Politeknik Negeri Semarang, 2015)
Purpose of the community service activity isto improve the quality of organic manuremade from the waste of milking cow cattleand the marketing management. Problemsolvingmethods used are teaching andtraining about the organic manure makingtechniques, packaging and the marketingmanagement. Community service activitiesshows the results, in accordance with themethod is expected that results from themanufacture of the organic manure productshowed that the participants can understandand practice the manufacture of the productas well, discuss various problems and themanufacture and marketing of the organicmanure product as well as suggestions /feedback from the instructor can beunderstood and accepted manufacturingpractices and extension yhe organic manureproduct carried out simultaneously showedeffective results.